DOI: 10.1007/978-3-540-68830-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Differential Evolution for the Offline and Online Optimization of Fed-Batch Fermentation Processes

Abstract: Summary. The optimization of input variables (typically feeding trajectories over time) in fed-batch fermentations has gained special attention, given the economic impact and the complexity of the problem. Evolutionary Computation (EC) has been a source of algorithms that have shown good performance in this task. In this chapter, Differential Evolution (DE) is proposed to tackle this problem and quite promising results are shown. DE is tested in several real world case studies and compared with other EC algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…However, when noisier settings were employed, the DE algorithm performance decreased. Using the same case studies and objectives (from Rocha et al 2007), Mendes et al (2008) performed online and offline optimizations of input variables by applying three distinct algorithms, namely DE, a real value EA, and a fully informed particle swarm (FIPS). The results obtained for the offline optimization indicated that DE/Rand/1/ bin has the best results, followed closely by DE/best/2/ bin and FIPS.…”
Section: Simple De Versions Used In Process Optimizationmentioning
confidence: 99%
“…However, when noisier settings were employed, the DE algorithm performance decreased. Using the same case studies and objectives (from Rocha et al 2007), Mendes et al (2008) performed online and offline optimizations of input variables by applying three distinct algorithms, namely DE, a real value EA, and a fully informed particle swarm (FIPS). The results obtained for the offline optimization indicated that DE/Rand/1/ bin has the best results, followed closely by DE/best/2/ bin and FIPS.…”
Section: Simple De Versions Used In Process Optimizationmentioning
confidence: 99%
“…important biological variables, such as substrate/nutrients concentrations). 24 Zuo and Wu 25 implemented (via simulation) a method to perform a semireal time optimization for the fed-batch cultivation of Bacillus thuringiensis. A hybrid neural network was used for modelling the process, whereas the genetic algorithm method was used for performing the optimization.…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid neural network was used for modelling the process, whereas the genetic algorithm method was used for performing the optimization. State variables were measured and the system was re-optimized every 1 h. Mendes et al 24 performed in silico studies on the implementation of on-line optimization to three case studies (fed-batch recombinant E-coli fermentation, fed-batch ethanol production, and a hybridoma reactor). These authors showed that metaheuristic optimization algorithms could solve the problem, even in the presence of simulated uncertainties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problems tackled are both benchmarks [11][12][13][14][15][16][17] and real-life [18][19][20][21]. Some examples for chemical engineering applications include: oxidation processes [22][23][24], energy, fuels and petrol derivatives [25][26][27][28][29], fermentation [30][31][32].…”
Section: Introductionmentioning
confidence: 99%